Effects of Mixing Tree Species on Soil Enzyme Activity and Carbon-Use Efficiency in Eroded Masson Pine Forest - WANG Man; JIANG Yongmeng; ZHANG Shiliang; ZHANG Jinxiu; ZHENG Linmin; ZENG Zhiwei; LYU Maokui; XIE Jinsheng (Shuitu Baochi Xuebao)
[Objective] Soil microbial metabolic efficiency profoundly affects soil nutrient cycling and soil carbon sequestration in the recovery process of eroded and degraded areas. However, it is unclear how tree species mixture affects soil extracellular enzyme stoichiometry and microbial carbon-utilization efficiency in single Pinus massoniana plantation in the eroded red soil area. [Methods] In this study, we used single P. massoniana plantation, and P. massoniana and Schima superba mixed plantation with different restoration years, determined the soil physicochemical properties, extracellular enzyme activity and phospholipid fatty acid markers of different forests, and calculated the soil enzyme stoichiometric ratio and microbial carbon-utilization efficiency (CUE). [Results] (1) With the increase of restoration years, soil acid phosphatase (AP) and β-glucosidase (βG) activities were significantly reduced, while C∶NEEA (βG∶NAG), vector length (VL) and vector angle (VA) of the mixed forest were lower than that of pure forest, while C∶PEEA (βG∶AP) and N∶PEEA (NAG∶AP) showed the opposite trend, indicating that long-term mixing is beneficial to alleviate the carbon limitation and phosphorus limitation of microorganisms. (2) Mixing was beneficial to improve CUE and significantly increased with the increase of forest age. Specifically, compared with that of Y39-CF and Y19-MF, CUE of Y39-MF significantly increased by 200.00% and 136.84%, respectively. (3) By analyzing the characteristics of soil enzyme activity and the relationship between CUE and environmental factors, it was found that soil carbon, nitrogen and phosphorus availability was an important influencing factor, mainly affecting AP activity, C∶PEEA, N∶PEEA, VL, VA and CUE, while the stoichiometric ratio of soil nutrients mainly affected βG activity and C∶NEEA. (4) The results of redundancy analysis (RDA) showed that the ratio of fungi and bacteria mainly affected the characteristics of soil enzyme activity and CUE in the mixed forest, while the main influencing factors in pure forest were actinomyces and Gram-negative bacteria. [Conclusion] Mixing tree species significantly improves forest soil nutrients, affects the release of soil extracellular enzymes, and improves CUE, and it is conducive to soil carbon sequestration. Therefore, the differences between pure forest and secondary forest should be considered in future management and research of P. massoniana forest.